Animal Colors - Godfrey, Rachel; Pitts, Sorrel (UK Ladybird Books, 2019)
What colors are the animals ? What colors are their homes ? Color helps some animals, because other animals cannot see them
Inspired by BBC Earth TV series and developed with input from BBC Earth natural history specialists
Science (Animals)
Keywords: Animals